Country-level governance, accounting standards, and tax avoidance: a cross-country study. Issue 3 (18th October 2019) - Zeng, Tao
Abstract : Purpose: The purpose of this paper is to examine the impact of country-level governance and accounting standards on corporate tax avoidance. Design/methodology/approach: This paper is an empirical work using a sample of listed companies from 36 countries. Findings: This paper finds that firms resident in countries with stronger country-level governance engage in less tax avoidance. Aspects of stronger country-level governance include higher government effectiveness and regulatory quality, and stronger enforcement of law and control of corruption. This paper also finds that firms adopting international accounting standards ( IFRS ) engage in less tax avoidance than those using local accounting standards. Further examination of the effect of interactions between country-level governance and the adoption of IFRS on tax avoidance finds that there is a substitute relationship between country-level governance and the adoption of IFRS . Social implications: This study has significant implications for policy makers, corporate management and academics. It documents that when a country implements governance targeting improving government effectiveness, enhancing regulatory quality, strengthening enforcement of laws and controlling corruption, this will lead to less corporate tax avoidance. It also shows that the adoption of IFRS will reduce corporate tax avoidance, probably by enhancing accounting quality and disclosure, and that the adoption of IFRS provides a bond mechanism in reducing tax avoidance in countries with weak governance. Originality/value: This paper is the first study to examine the impact of country-level governance on tax avoidance at the corporate level. It is also the first study to examine how country-level governance interplays with IFRS in shaping firms' tax avoidance activities.